SPE International Symposium and Exhibition on Formation Damage Control 2006
DOI: 10.2118/98333-ms
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Results With a New Environmentally Acceptable, Oil-Soluble Chemical for Sand Consolidation: From Laboratory Experiments to Field Application

Abstract: The conceptual idea of chemical sand consolidation is to give the formation some additional residual strength in order to enhance the maximum sandfree rate (MSFR). Sand production in weakly consolidated reservoirs will occur when stresses in the well/perforation tunnel walls are large enough to disrupt the binding between the individual sand grains. This will generate a plasticised layer of sand in the near well bore area. The layer will erode by the produced fluid and may be transported to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The field experience at Heidrun with the chemical has shown that correct placement is critical when it comes to performance with regards to increasing the MSFR. This is in accordance with previous field experience with the sand consolidation chemical 6 . Although difficult to deduce, reduction in PI does not seem to be a major concern in these treatments.…”
Section: Resultssupporting
confidence: 93%
“…The field experience at Heidrun with the chemical has shown that correct placement is critical when it comes to performance with regards to increasing the MSFR. This is in accordance with previous field experience with the sand consolidation chemical 6 . Although difficult to deduce, reduction in PI does not seem to be a major concern in these treatments.…”
Section: Resultssupporting
confidence: 93%
“…Its use also leads to increased consolidated system resistance to chemical attack and degradation (Harrisberger et al 1971). In particular, organosilanes coupling agents family have been applied alone (Kotlar et al 2005, Kotlar et al 2006) and mixed with resins (Walther et al 1966;Spain 1967;Nguyen 2007).…”
Section: Overview Of Chemical Sand Consolidation (Csc) Technologymentioning
confidence: 99%
“…The chemistry and details regarding the chemical can be found in other publications [9,12]. The stabilized sand matrix can therefore withstand higher hydrodynamic forces from the fluid flow and thereby prevent the erosion and transport of sand grains into the wellbore and possibly all the way to the process facilities top-side.…”
Section: Experimental and Proceduresmentioning
confidence: 99%
“…These are described elsewhere [9,12] Case histories. Strength of 50 bar differential pressure can be obtained with low concentrations of organosilane.…”
Section: Sand Grain ---------Covalent Binding--------sand Grainmentioning
confidence: 99%